Societal economic burden of multiple sclerosis and cost-effectiveness of disease-modifying therapies - Simoens, Steven (Frontiers in Neurology, 2022)
Background In an era of scarce resources, policy makers, neurologists and other stakeholders need to be aware of the economic burden of multiple sclerosis and the cost-effectiveness of disease-modifying therapies. The aim of this article is to provide a mini-review of these health economic facets of multiple sclerosis. Methods An umbrella review was conducted by searching PubMed and Google Scholar from 2002 until June 2022 for peer-reviewed systematic and narrative literature reviews. Results An extensive body of evidence corroborates that multiple sclerosis is associated with a substantial economic burden within and outside the health care sector, that costs of secondary progressive multiple sclerosis exceed those of relapsing-remitting multiple sclerosis, that costs increase with disease severity and are influenced by the occurrence of relapses and therapy adherence. However, cost estimates and their breakdown into various components vary between countries. Economic evaluations show that disease-modifying therapies for relapsing-remitting multiple sclerosis are generally not cost-effective, but these results depend on the local setting. Cost-effectiveness of disease-modifying therapies improves when a societal perspective is taken and efficacy does not wane over a lifetime horizon, when oral administration forms or dosing strategies requiring less maintenance are introduced, and when generic versions enter the market. Reimbursement recommendations related to disease-modifying therapies also differ between countries. Conclusion The local context matters when calculating the societal economic burden of multiple sclerosis and the cost-effectiveness of disease-modifying therapies.